China in the twenty-first century : politics, economy, and society - Aoyama Gakuin Daigaku (Tokyo : United Nations University Press, 1997)
China has experienced tremendous change during the era of the People's Republic, particularly during the past 15 years, a period in which it has begun a shift from a centrally planned economy to a market-oriented system. This book, based on an international symposium held at Aoyama Gakuin University, Tokyo, attempts to form a picture of the landscape of China in the twenty-first century.
China : moving towards the twenty-first century / Rong Yiren -- China in the twenty-first century / Helmut Schmidt -- History, politics, and the sources of economic growth : China and the East Asian way of growth / Dwight H. Perkins -- China's "open door" and the internal development in perspective of the twenty-first century / Shigeru Ishikawa -- China's economic reform : successes, challenges, and prospects for the twenty-first century / Liu Guoguang -- On the adjustment of China's industrial structure : the lateral unification of automobile industries / Chen Qiaosheng -- Managerial reform of Chinese state-owned enterprises : a shift to joint stock corporation / Mitsuo Morimoto -- Asia since the Cold War and the new international order : the historical perspective and future prospects / Satoshi Amako -- Prospects on social development / Lu Xueyi -- Chinese democracy and constitutional development / Lucian W. Pye.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: ASEAN; China -- Economic conditions -- 1976-2000.; China -- Politics and government -- 1976-; Economic forecasting -- China -- Congresses; China -- Economic conditions -- 1976-2000 -- Congresses; China -- Social conditions -- 1976-2000 -- Congresses; Prévision économique -- Chine -- Congrès.; Chine -- Conditions économiques -- 1976-2000 -- Congrès.; Chine -- Politique et gouvernement -- 1976- -- Congrès.; Chine -- Conditions sociales -- 1976-2000 -- Congrès.; Chine -- Conditions économiques -- 1976-2000.; POLITICAL SCIENCE -- Economic Conditions; BUSINESS & ECONOMICS -- Economics -- Comparative; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; Social conditions; Economic forecasting; Economic history; Politics and government; China; Wirtschaft; Gesellschaft; Politik; China; Economische groei; Economische situatie; Sociaal-economische ontwikkeling; Prévision économique -- Chine; Prévision sociale -- Chine; Chine -- Conditions économiques -- 1976-2000.; Chine -- Politique et gouvernement -- 1976- ...; Chine -- Conditions sociales -- 1976-2000.; ECONOMIC DEVELOPMENT; ECONOMIC REFORM; INDUSTRIAL REDEPLOYMENT; AUTOMOBILE INDUSTRY; STOCK COMPANIES; SOCIAL DEVELOPMENT; CHINA; NEW INTERNATIONAL ECONOMIC ORDER; DEMOCRACY; Since 1976; Congress; proceedings (reports); Conference papers and proceedings; Congressen (vorm); Conference papers and proceedings; Actes de congrès.